Penggunaan Conventional Ultrafiltration selama Cardiopulmonary Bypass untuk Mencegah Terjadinya Acute Kidney Injury Paska Operasi Jantung - Yuniyas Ihsanidar; Elly Nurachmah (Journal of Telenursing (JOTING), 2023)
This study aims to identify the relationship between the use of conventional ultrafiltration and the incidence of postoperative acute kidney injury associated with the help of a cardiopulmonary bypass machine. The method used is a systematic review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart to obtain five selected literature. The results showed a relationship between conventional ultrafiltration fluid volume shifts and the incidence of post-cardiac surgery acute kidney injury. In conclusion, ultrafiltration fluid volume displacement > 32 mL/kg will increase the risk of acute kidney injury after cardiac surgery. Keywords: Acute Kidney Injury, Cardiopulmonary Bypass, Conventional Ultrafiltration, Heart Surgery